Metallic trace element concentrations, vertical patterns and environmental implications in soils under the “cabruca” agroforestry system of Brazil's largest cocoa-producing region - Tatiana Reis dos Santos Bastos; João Carlos Medeiros; Clistenes Williams Araújo do Nascimento; Paula Nascimento Alves; Pâmalla Graziely Carvalho Morais; Glécio Machado Siqueira; Maria Eugênia Ortiz Escobar; Kaique Mesquita Cardoso; Thomas Vincent Gloaguen; Simone Aparecida da Silva Lins; Cácio Luiz Boechat (Science of The Total Environment, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Hospital Indoor Air as a Reservoir of Opportunistic Filamentous Fungi: Species Diversity and Antifungal Susceptibility - Jhully Pimentel; Glaucia Queiroz dos Santos; Thiago Oliveira Condé; Simone Bravim Maifrede; Thaís Oliveira Scardua; Rubia Miossi; Tatiana Alves dos Reis; Kelly Ishida; Creuza Rachel Vicente; Sarah Santos Gonçalves (Current Microbiology, 2026)
Filamentous fungi are common airborne contaminants in hospitals, posing significant risks to immunocompromised patients. This study assessed the diversity, seasonal distribution, and antifungal susceptibility of airborne filamentous fungi, with a focus on Aspergillus spp., in two inpatient wards of a tertiary hospital in southeastern Brazil. Air samples were collected seasonally from November 2022 to September 2023 using a six-stage Andersen sampler. Fungal isolates were identified based on macro- and micromorphological characteristics, and Aspergillus spp. were further characterised by β-tubulin gene sequencing. In vitro susceptibility to amphotericin B (AMB), itraconazole (ITR), voriconazole (VOR), posaconazole (POS), and anidulafungin (AFG) was evaluated following CLSI guidelines. A total of 583 filamentous fungi were isolated, with Penicillium , Cladosporium and Aspergillus as the most prevalent genera. Fungal concentrations were higher in humidified air and decreased after installation and maintenance of the air-conditioning system. Fourteen Aspergillus species were identified across eight sections, including emerging and cryptic taxa such as A . subramanianii , A . sclerotiorum and A . alboviridis . Resistance to ITR was detected in one isolate of A . fumigatus and one of A . flavus , while isolates from emerging species of the section Circumdati exhibited elevated MICs for AMB and triazoles. All isolates demonstrated low AFG MECs. The study highlights the importance of routine environmental surveillance and antifungal susceptibility testing in hospital settings. The detection of potentially resistant Aspergillus species in hospital air emphasises the need to enhance ventilation, monitoring, and diagnostic capabilities to mitigate the risks of healthcare-associated fungal infections.

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Assessment of some potentially toxic elements on a watershed-scale through an integrated chemical and biological monitoring framework in the Caatinga-Atlantic Forest ecotone, Northeast Brazil - Kaíque Mesquita Cardoso; Clístenes Williams Araújo do Nascimento; Douglas Gonçalves da Silva; Simone Aparecida da Silva Lins; Maria Eugenia Ortiz Escobar; Pâmalla Graziely Carvalho Morais; Tatiana Reis dos Santos Bastos; Cácio Luiz Boechat (Environmental Science and Pollution Research, 2026)
The concern for water quality is a critical issue in many countries around the world. The monitoring of water resources should be implemented to ensure water management, especially when dealing with already impacted systems. Urbanization is an impactful type of activity that contributes to the release of potentially toxic elements (PTEs) into the ecosystems. The identification of plant species with the ability to tolerate high levels of contaminants could be an alternative to remove contaminants from these environments and to evaluate the plants as bioindicators. The objective of this study was to assess the surface water and sediment quality of the Verruga River and test the aquatic macrophytes’ potential as biomonitors of some PTEs: Cd, Co, Cr, Cu, Mn, Ni, Pb, and Zn. Ten sampling points were included in the study, ranging from the source to the mouth of the river. Samples of surface water, sediments, and macrophytes were collected. In situ and laboratory analyses were performed. Direct readings of PTEs in surface water, extracts from plants and sediments were performed using ICP-OES. Quality reference guides were used. The mobility of the elements can be better visualized by the correlations between the parameters of the sediments than of the water. Concentration of Cd, Cu, Mn, Ni, Pb and Zn in surface water, sediments and aquatic plants reached different levels and some parameters exceeded guidelines on environmental quality. The species Heteranthera reniformis and Eichhornia crassipes are promising macrophytes for studies on biomonitoring of PTEs in the aquatic environment of the Verruga River. Graphic Abstract

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Antioxidant activity and volatile profile of Lobularia maritima flowers cultivated in Brazil - Iná Tharcelle de Carvalho Silveira; Camila Gonçalves Rodrigues; Vinícius Tadeu da Veiga Correia; Simone Novaes Reis; Valéria Aparecida Vieira Queiroz; Christiano Vieira Pires; Liliane Crislaine dos Santos Souza; Lanamar de Almeida Carlos (International Journal of Gastronomy and Food Science, 2026)

Ecotoxicological effects of drilling cuttings waste from oil wells: sensitivity of soil invertebrates and plants - Dara C. M. V. P. da Cruz; Higor E. F. Lorin; Fabrielle P. dos Reis; Cibele A. de Costa; Simone B. da Fontoura; Heraldo N. de Souza; Everaldo Zonta; Júlia C. Niemeyer (Ecotoxicology, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Characterization and pre-selection of Myrciaria dubia (Kunth) McVaugh (Myrtaceae) clones with desirable traits for crossbreeding in Eastern Amazonian germplasm - Olívia Domingues Ribeiro; Walnice Maria Oliveira do Nascimento; Amanda Reis da Silva; Mônica Falcão-da-Silva; Muhammad Zafar; Mozaniel Santana de Oliveira; Ely Simone Cajueiro Gurgel (Genetic Resources and Crop Evolution, 2026)

Development, growth, and flower production of cut sunflower under tropical, subtropical, and temperate environments - Regina Tomiozzo; Lilian Osmari Uhlmann; Leosane Cristina Bosco; Márkilla Zunete Beckmann-Cavalcante; Petterson Baptista da Luz; José Carlos Sorgato; Simone Novaes Reis; Lívia Mendes de Carvalho; Anelise Tessari Perboni; Luana Moraes da Luz; Heberte Fernandes de Figueredo; Sebastião Marcos Silva Valentim; et al. (Horticulture, Environment, and Biotechnology, 2025)

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Detection via high-throughput sequencing of a rare host jump event of a bipartite weed-infecting begomovirus to tomato - Luciane de Nazaré Almeida dos Reis; Maria Esther de Noronha Fonseca; Izaías Araújo de Oliveira; Simone Graça Ribeiro; Leonardo Silva Boiteux; Rita de Cássia Pereira-Carvalho (Journal of Plant Pathology, 2025)

Economic impacts of an urban gully are driven by land degradation - Caiubi Emanuel Souza Kuhn; Fábio Augusto Gomes Vieira Reis; Simone Andrea Furegatti; Christiane Zarfl; Anna Sílvia Palcheco Peixoto (Natural Hazards, 2024)
This study carries out the first evaluation of the impacts of ravines and gullies in urban areas in Brazil considering environmental damage, such as costs related to land restoration and erosion control, infrastructure destruction, economic losses and income losses related to property and urban land taxes. In this study, the city of Bauru, Brazil, has been selected as study site, where three areas were chosen due to the large impact that ravines and gullies have caused over the past two decades. Our analysis indicates that the total damage exceeds US$ 173 million and is mainly related to land degradation. The cost of replacing the eroded soil in these three areas is estimated at approximately US$ 13.3 million. Furthermore, according to our analysis, urban areas affected by ravines and gullies represent problems similar to brownfields. The assessment of the impacts and challenges associated with urban ravines and gullies can help promote accountability by those responsible for their initiation and may contribute to decreasing the development of new eroded areas.

Supplementation of l-arginine in pregnant gilts affects the protein abundance of DNMT1 in 35-day fetuses - Karine Assis Costa; Lívia Maria dos Reis Barbosa; Daniele Botelho Diniz Marques; Walmir da Silva; Breno Soares Camilo; Domingos Lollobrigida de Souza Netto; Alysson Saraiva; José Domingos Guimarães; Simone Eliza Facioni Guimarães (Animal Reproduction Science, 2024)

Impact of the extreme 2015-16 El Niño climate event on forest and savanna tree species of the Amazonia-Cerrado transition - Nayane C.C.S. Prestes; Beatriz S. Marimon; Paulo S. Morandi; Simone M. Reis; Ben Hur Marimon Junior; Wesley J.A. Cruz; Edmar A. Oliveira; Lucas H. Mariano; Fernando Elias; Denilson M. Santos; Adriane Esquivel-Muelbert; Oliver L. Phillips (Flora, 2024)

The Resistance of Bacillus Spores: Implications for the Strain-Specific Response to High-Performance Disinfectants - Simone Sommerfeld; Lidianne Fabricia dos Santos Tomais; Lara Reis Gomes; Maysa Vitória Cunha Silva; Isabelle Ezequiel Pedrosa; Danielle Silva Vieira; Arthur Campoi Peluco; Vasco Ariston Carvalho de Azevedo; Belchiolina Beatriz Fonseca (Current Microbiology, 2024)

Detection and molecular characterization of a novel mitovirus associated with Passiflora edulis Sims - Yam Sousa Santos; Andreza Henrique Vidal; Emanuel Felipe Medeiros Abreu; Isadora Nogueira; Fábio Gelape Faleiro; Cristiano Castro Lacorte; Fernando L. Melo; Magnólia de Araújo Campos; Rafael Reis de Rezende; Tulio Morgan; Arvind Varsani; Poliane Alfenas-Zerbini; et al. (Archives of Virology, 2024)

Mindful eating questionnaire: Validation and reliability in Brazilian adults with type 2 diabetes mellitus - Danielle Aparecida Caetano Rodrigues; Aline Marcadenti; Rachel H.V. Machado; Angela C. Bersch-Ferreira; Edilaine C.S. Gherardi-Donato; Driele Quinhoneiro; Jussara Carnevale de Almeida; Viviane Sahade Souza; Simone Raimondi de Souza; Fernanda Michielin Busnello; Daniela Corrêa Ferreira; Josefina Bressan; et al. (Appetite, 2024)

Revamping kombucha production: Achieving consistency and probiotic potential through a tailor-made microbial consortium - Mariana Fensterseifer Fabricio; Bruna Krieger Vargas; Bruna Tischer; Roger Wagner; Stephanie Reis Ribeiro; Nereida Cordeiro; Simone Hickmann Flôres; Marco Antônio Záchia Ayub (International Journal of Gastronomy and Food Science, 2023)

Novel plant-associated genomoviruses from the Brazilian Cerrado biome - Flávia Milene B. Nery; Josiane G. Batista; Felipe Fochat. S. Melo; Simone G. Ribeiro; Leonardo S. Boiteux; Fernando L. Melo; Juliana Gabrielle I. Silva; Luciane de Nazaré A. Reis; Rita C. Pereira-Carvalho (Archives of Virology, 2023)

Winter heat waves characteristics associated with downslope windstorm in south Brazil - Cinara Ewerling da Rosa; Michel Stefanello; Nicolle Cordero Simões dos Reis; Douglas Stefanello Facco; Simone Teleginski Ferraz; Nathalie Tissot Boiaski; Dirceu Luis Herdies; Gervásio Annes Degrazia (International Journal of Climatology, 2023)
The air temperature anomaly was analysed in 16 consecutive winters from 2004 to 2019 in southern Brazil using reanalysis data and hourly atmospheric observations. In this study, 13 heat wave (HW) episodes were identified using the percentile methodology. All identified episodes are associated with the occurrence of a downslope windstorm known as Vento Norte (VNOR; Portuguese for ‘North Wind’). The VNOR is characterized by a sharp increase in air temperature combined with constant, strong, gusty winds from the north and a drop in relative humidity. The average duration was about 5 days for HW and 18 h for VNOR being than in 59.5% of the HW hours, the VNOR windstorm was also detected. The main atmospheric variables were compared during the periods of winter, HW and the VNOR windstorm. The analysis showed that HW alters local weather and climate conditions, with the more pronounced features associated with the VNOR flow. A more detailed investigation comparing the atmospheric variables collected north and south of an abrupt change in terrain altitude (400 m) revealed that the main cause of the amplification of the atmospheric variable anomalies in the centre of the state of Rio Grande do Sul was the simultaneous occurrence of HW and VNOR.

Stress-associated β -glucan administration stimulates the TLR – MYD88 – NFKB1 signaling pathway in Nile tilapia (Oreochromis niloticus) - Simone Andrea de Assis Beneti; Ingrid Camargo dos Reis; Camino Fierro-Castro; Basia Schlichting Moromizato; Gustavo do Valle Polycarpo; Celso Tadao Miasaki; Jaqueline Dalbello Biller (Fish & Shellfish Immunology, 2023)

Mitochondrial swelling in cardiomyocytes: Insights from a murine model of Tityus serrulatus scorpion envenomation - Mouzarllem Barros Reis; Simone Gusmão Ramos; Lenaldo Branco Rocha; Lúcia Helena Faccioli (Toxicon, 2023)

Morpho-anatomical traits and leaf nutrient concentrations vary between plant communities in the Cerrado–Amazonia transition? - Igor Araújo; Marina C. Scalon; Izabel Amorim; Imma Oliveras Menor; Wesley J.A. Cruz; Simone Matias Reis; Priscila F. Simioni; Beatriz S. Marimon (Flora, 2023)

The silent extinction of freshwater mussels in Portugal - Manuel Lopes-Lima; Joaquim Reis; Maria G. Alvarez; Pedro M. Anastácio; Filipe Banha; Pedro Beja; Paulo Castro; Mafalda Gama; Maria G. Gil; André Gomes-dos-Santos; Fernando Miranda; Joana Garrido Nogueira; et al. (Biological Conservation, 2023)

Streams in the Mediterranean Region are not for mussels: Predicting extinctions and range contractions under future climate change - Janine P. da Silva; Ronaldo Sousa; Duarte Vasconcelos Gonçalves; Rafael Miranda; Joaquim Reis; Amílcar Teixeira; Simone Varandas; Manuel Lopes-Lima; Ana Filipa Filipe (Science of The Total Environment, 2023)

Drawing transformation pathways for making use of joint effects of food and energy production with biodiversity agriphotovoltaics and electrified agricultural machinery - Anne-Kathrin Schneider; Felix Klabunde; Lennart Buck; Maren Ohlhoff; Larissa Reis; Madita Olvermann; Simone Kauffeld; Bernd Engel; Gerhard Glatzel; Boris Schröder; Ludger Frerichs (Journal of Environmental Management, 2023)

Association of Fructo-oligosaccharides and Arginine Improves Severity of Mucositis and Modulate the Intestinal Microbiota - Maria Emília Rabelo Andrade; Luisa Martins Trindade; Paola Caroline Lacerda Leocádio; Jacqueline Isaura Alvarez Leite; Diego Carlos dos Reis; Geovanni Dantas Cassali; Tales Fernando da Silva; Rodrigo Dias de Oliveira Carvalho; Vasco Ariston de Carvalho Azevedo; Gregório Grama Cavalcante; Jamil Silvano de Oliveira; Simone Odília Antunes Fernandes; et al. (Probiotics and Antimicrobial Proteins, 2023)

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

Iron(II) sulfate and pH decrease seed germination and seedling growth and alter nutrient and polyamine contents in Cedrela fissilis Vellozo (Meliaceae) - Benjamim Valentim da Silva; Tadeu dos Reis de Oliveira; Victor Paulo Mesquita Aragão; Almy Junior Cordeiro de Carvalho; Marta Simone Mendonça Freitas; Vanildo Silveira; Alessandro Coutinho Ramos; Claudete Santa-Catarina (Brazilian Journal of Botany, 2023)

Ethyl acetate fractions of Myrciaria floribunda, Ocotea pulchella, and Ocotea notata exhibit promising in vitro activity against Sporothrix brasiliensis isolates with low susceptibility to itraconazole - Lais Cavalcanti dos Santos Velasco de Souza; Nathália Faria Reis; Lucas Martins Alcântara; Simone Rocha Leal da Silveira Souto; Bruno de Araújo Penna; Renan Caetano Souza Santos; Bruno Kaufmann Robbs; Francisco Paiva Machado; Helena Carla Castro; Ricardo Luiz Dantas Machado; Leandro Rocha; Andréa Regina de Souza Baptista (Brazilian Journal of Microbiology, 2023)

Chicken embryos are a valuable model for the selection of Bacillus subtilis for probiotic purposes - Thais Fernanda Martins dos Reis; Patricia Giovana Hoepers; Vasco Ariston de Carvalho Azevedo; Gabriela Ribeiro da Silva; Fabiana Oliveira Notário; Maria Cecília Soares; André Eduardo Schlemper; Ícaro Mendonça Costa; Nina Dias Coelho-Rocha; Mylla Spirandelli da Costa; Simone Sommerfeld; Alessandra Aparecida Medeiros-Ronchi; et al. (Archives of Microbiology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Cointegrated land use and CO2 emissions—the silent Columbian cattle revolution - David Roberto Patiño-Domínguez; Nadja Simone Menezes Nery de Oliveira; Paulo Reis Mourao (Environmental Science and Pollution Research, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

7-Chloro-4-(Phenylselanyl) Quinoline with Memory Enhancer Action in Aging Rats: Modulation of Neuroplasticity, Acetylcholinesterase Activity, and Cholesterol Levels - Anelise Barth; Ane G. Vogt; Angélica S. dos Reis; Mikaela P. Pinz; Roberta Krüger; William B. Domingues; Diego Alves; Vinicius F. Campos; Simone Pinton; Natália Paroul; Ethel A. Wilhelm; Cristiane Luchese (Molecular Neurobiology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Analysis of fungal contamination in vehicle air filters and their impact as a bioaccumulator on indoor air quality - Simone Aquino; José Eduardo Alves de Lima; Ana Paula Branco do Nascimento; Fabrício Caldeira Reis (Air Quality, Atmosphere & Health, 2018)

Savanna turning into forest: concerted vegetation change at the ecotone between the Amazon and “Cerrado” biomes - Fábio Barbosa Passos; Beatriz Schwantes Marimon; Oliver L. Phillips; Paulo Sérgio Morandi; Eder Carvalho das Neves; Fernando Elias; Simone Matias Reis; Bianca de Oliveira; Ted R. Feldpausch; Ben Hur Marimon Júnior (Brazilian Journal of Botany, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Downregulation of histone methyltransferase EHMT2 in CD4+ T-cells may protect HTLV-1-infected individuals against HAM/TSP development - Camila Schoueri Colaço; Adriano Reis de Matos; Martha Silva Estrêla; Maurício Cristiano Rocha-Júnior; Kátia Kaori Otaguiri; Evandra Strazza Rodrigues; Osvaldo Massaiti Takayanagui; Dimas Tadeu Covas; Simone Kashima; Fabio Pittella Silva; Rodrigo Haddad (Archives of Virology, 2017)

Erratum to: Nitrogen dynamics in subtropical fringe and basin mangrove forests inferred from stable isotopes - Carla Roberta Gonçalves Reis; Gabriela Bielefeld Nardoto; André Luis Casarin Rochelle; Simone Aparecida Vieira; Rafael Silva Oliveira (Oecologia, 2017)

Nitrogen dynamics in subtropical fringe and basin mangrove forests inferred from stable isotopes - Carla Roberta Gonçalves Reis; Gabriela Bielefeld Nardoto; André Luis Casarin Rochelle; Simone Aparecida Vieira; Rafael Silva Oliveira (Oecologia, 2017)

Resistance to fire and the resilience of the woody vegetation of the “Cerradão” in the “Cerrado”–Amazon transition zone - Simone Matias Reis; Edmar Almeida de Oliveira; Fernando Elias; Letícia Gomes; Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon Junior; Eder Carvalho das Neves; Bianca de Oliveira; Eddie Lenza (Brazilian Journal of Botany, 2017)

Tracking the expansion of the American mink (Neovison vison) range in NW Portugal - Diana C. Rodrigues; Luciana Simões; Jacinta Mullins; Simone Lampa; Raquel C. Mendes; Carlos Fernandes; Rui Rebelo; Margarida Santos-Reis (Biological Invasions, 2015)

A human-like H1N2 influenza virus detected during an outbreak of acute respiratory disease in swine in Brazil - Rejane Schaefer; Raquel Rubia Rech; Danielle Gava; Mauricio Egídio Cantão; Marcia Cristina da Silva; Simone Silveira; Janice Reis Ciacci Zanella (Archives of Virology, 2015)

Neuroparacoccidioidomycosis (NPCM): Magnetic Resonance Imaging (MRI) Findings - Fabiano Reis; Priscila Pimentel Collier; Thiago Ferreira Souza; Guilherme Pinheiro Lopes; Eduardo Bronzatto; Nivaldo Adolfo Silva Junior; Ricardo Mendes Pereira; Simone Appenzeller (Mycopathologia, 2013)